Policy dilemmas for ASEAN developing countries arising from the tariff moratorium on electronically transmitted goods - Manuel F. Montes; Peter Lunenborg (South Centre, 2023)
This paper examines the policy dilemmas facing developing countries in ASEAN in working within, and participating in, international negotiations toward making permanent the WTO tariff moratorium on duties applicable to electronically transmitted goods. In the context of ASEAN's countries' trade-oriented development strategies, the analysis considers the moratorium's impact on tariff revenues, economic performance, and industrial development prospects. The paper presents estimates of tariff impacts and studies the national policy implications of the moratorium. An extension of the moratorium would establish a special regime for a class of goods whose components are contentiously defined but with a potential of being an important source of tariff revenue and of having an impact on industrial development in the future for developing ASEAN countries. This special regime for electronically transmitted goods cannot be justified as a global public good and is unnecessary. The removal of the regime would restore national space in developing ASEAN countries and allow them to obtain tariff revenues from the trade of these goods and to upgrade domestic capabilities in participating in the digital economy.
Keywords: 300; Association of Southeast Asian Nations (ASEAN); Digital Economy; Digital Trade; E-commerce; Electronically Transmitted Goods; Industrial Development; Moratorium; Tariffs; World Trade Organization (WTO)